(untitled) (One Health & Risk Management, 2024)
Antimicrobial resistance (AMR) poses a threat to global health, thus requiring a collaborative effort from professionals across diverse disciplines to achieve optimal health outcomes for humans, animals, plants, and the environment. Therefore, it is essential to recognize that effective planning and implementation of sustainable solutions will only be achievable when multidisciplinary research teams, including expertise beyond health sciences, such as implementation scientist and economists, are regarded as a primary source of high-quality evidence rather than merely a supplementary or unconventional approach to scientific research. For example, a multidisciplinary and One Health approach involves not only creating a comprehensive system for monitoring AMR trends in humans, animals, and the environment but also identifying the most cost-effective methods, as well as understanding the factors that motivate various stakeholders to change their behavior and provide high-quality, timely data. Besides, integrating findings from cost-effectiveness studies into broader AMR programs, enables stakeholders to make informed decisions that would optimize health outcomes while minimizing economic burdens. The One Health and Risk Management journal =promotes interdisciplinary collaboration and supports innovative research within One Health field, particularly regarding AMR. Thus, I would like to sincerely congratulate the colleagues from Republic of Moldova for their remarkable achievement in publishing the fourth issue of this national journal. This initiative encourages collaboration, stimulate innovative research, as well as contribute significantly to the overall global efforts in tackling the AMR-related challenges. Enjoy reading a good compilation of multidisciplinary work.